Reconstruction of Regulations for Making Birth Certificates for Children Born out of Wedlock Without a Marriage Certificate Based on Islamic Justice Values - Innash, Ar-Rahiim; Mashdurohatun, Anis; Endah, Sri (Research Horizon, 2024)
Marriage is an important moment in human life that involves not only individuals, but also society. In the legal context, marriage creates a legal bond, resulting in a number of obligations and rights between husband, wife, and children. Birth certificates of illegitimate children are a crucial issue, especially in the context of legal justice in Indonesia. This study aims to analyze the implementation of regulations related to birth certificates of illegitimate children without a marriage certificate, with a focus on existing weaknesses and how Islamic justice values ​​can be integrated. The research method used is a descriptive analytical approach with primary and secondary data collection, including interviews and observations. The results of the study indicate that there are still many illegitimate children in Semarang City who do not have birth certificates, caused by factors such as inconsistencies in Family Card data, low public awareness, and slow administrative processes. In addition, the social stigma that considers illegitimate children as illegitimate children hinders the protection of their rights. Therefore, it is necessary to increase legal awareness and improve the administrative system by the government to ensure justice and protection for all children, in accordance with the values ​​of Pancasila which emphasize social justice. This study is expected to contribute ideas to the development of civil law in Indonesia.